REPRESENTASI KORBAN REVENGE PORN DALAM FILM “LIKE & SHARE” MELALUI ANALISIS SEMIOTIKA ROLAND BARTHES - auliya, naufal; oniarianto (The Commercium, 2025)
The film "Like & Share" directed by Gina S. Noer is a deep portrayal of the impact of sexual violence, particularly revenge porn, on female adolescent victims. The film depicts the dominance of the perpetrator and the powerlessness of the victim, while revealing patriarchal and misogynistic realities. Perpetrators often escape the punishment they deserve, while victims are frequently blamed or subjected to victim blaming. Through Roland Barthes' semiotic analysis, this study examines the representation of sexual violence in the film. Using a qualitative method, the researcher investigates the academic conditions through a critical descriptive approach. It is hoped that this research will make a valuable contribution to Communication Studies and raise awareness and social sensitivity to issues of sexual violence and its impact. Film serves as a tool for artists and filmmakers to express ideas and stories that have the power to influence society.